Sucessão geracional em propriedades rurais de associados a cooperativas agropecuárias: uma abordagem sobre jovens mulheres - Weber, Camila (2020)
Since the middle of the 20th century, family production units have experienced constraints, in the face of intense rural youth migratory flux to the urban centers. This scenario conditions to the understanding of different decisions made by these young, reverberating in the social and economic reproduction of the rural properties in which they are inserted. Different approaches present significant distinctions between men and women in the rural ambit, women are found at a disadvantage level, and therefore, decide when possible, to migrate to the urban centers in order to obtain their autonomy and independent income. Between innumerable elements conditioning the rural youth to migration, a main problem linked to it is centered on the continuity of the rural through the process of generational succession, which is the practice of daughters assuming from their parents the control of the business’ management, patrimony and property continuation. Given the background, this study’s main objective is the analysis of succession dynamics of young women within rural properties that are part of agricultural cooperatives of different productive segments in the Rio Grande do Sul state. The young women, ages ranging from 18 to 30 years old, are associates or daughters of cooperative associates, and live in the Northwest and Middle Eastern regions of the state. The research is qualitative and quantitative, utilizing semi-structured interviews as the way of collecting data. Procedure for data examination was the analysis of content. Were carried out 56 interviews and the young women were chosen meeting the criteria proposed by this study. In the view of the correspondents, the prototype that women participating in the rural environment is conditioned to activities and chores deemed as feminine, less heavy, less demanding, possessing no decision in the management, is not a reality anymore in face of the activities they actually develop on the property. These young women stand out to a greater participation in activities and property’s decisions, they have opted to remain in the rural, motivated by will and fondness of the agricultural work, beyond the search for knowledge through studies that have allowed them to return to the properties with improved education. The fact is that they possess the opportunity of opinion and decision over the property’s management, however is also noted that they may give opinion, nevertheless the final word will be given by the father, which in a certain way repels them from the management and consequently from the succession process, giving area for the young women to search for their own individual income and autonomy, (since the majority is required to ask their parents for money when needed), leaving the rural activities, although still residing in the rural, but choosing to work in the city. Albeit the research data have shown that the young women are inserted in the succession process and, the majority, in one type of activity, it has been observed the increasing participation of their partners/husbands that have come to the property, exerting labor on it and in some cases assuming the role of generational successors in place of their wives. Furthermore, the study makes evident the social and economic importance that agricultural cooperatives possess regarding the succession dynamics within rural properties through actions targeting local and regional development, actions that have been perceived by the majority of the young women. Women have pointed as small the actions aimed at them, linking other elements as decisive to guaranteeing that their fulfilment as generational successors occurs in a fluent and planned manner.